Digital radiography for determination of primary tooth length: in vivo and ex vivo studies - Basso, Maria Daniela; Jeremias, Fabiano [UNESP]; Cordeiro, Rita de Cássia Loiola [UNESP]; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP] (Wiley, 2015)
Background. Methods for determining the root canal length of the primary tooth should yield accurate and reproducible results. In vitro studies show some limitations, which do not allow their findings to be directly transferred to a clinical situation. Aim. To compare the accuracy of radiographic tooth length obtained from in vivo digital radiograph with that obtained from ex vivo digital radiograph. Method. Direct digital radiographs of 20 upper primary incisors were performed in teeth (2/3 radicular resorption) that were radiographed by an intraoral sensor, according to the long-cone technique. Teeth were extracted, measured, and mounted in a resin block, and then radiographic template was used to standardise the sensor-target distance (30 cm). The apparent tooth length (APTL) was obtained from the computer screen by means of an electronic ruler accompanying the digital radiography software (CDR 2.0), whereas the actual tooth length (ACTL) was obtained by means of a digital calliper following extraction. Data were compared to the ACTL by variance analysis and Pearson’s correlation test. Results. The values for APTL obtained from in vivo radiography were slightly underestimated, whereas those values obtained from ex vivo were slightly overestimated. No significance was observed between APTL and ACTL. Conclusion. The length of primary teeth estimated by in vivo and ex vivo comparisons using digital radiography was found to be similar to the actual tooth length.